Hereditary Combined Deficiency of the Vitamin K-Dependent Coagulation Factors - Raharimanana, Alexandre; Cunat, Séverine; Falaise, Céline; Oudot, Caroline; Fournel, Alexandra; Dargaud, Yesim (Hämostaseologie, 2025)
Hereditary combined vitamin K-dependent coagulation factor deficiency (VKCFD) is an extremely rare autosomal recessive genetic disorder characterized by deficiencies in vitamin K-dependent coagulation factors and natural anticoagulants. The condition presents with a spectrum of bleeding symptoms ranging from mild to severe, often beginning in the neonatal period. These bleeding episodes can be particularly severe and even life-threatening, occurring spontaneously or during surgery. In addition to bleeding problems, individuals with VKCFD may experience a variety of non-hemostatic problems, including skeletal deformities, cardiovascular abnormalities, and skin conditions.VKCFD is caused by variants in the genes encoding either γ-glutamyl carboxylase or the vitamin K 2,3-epoxide reductase complex. Both proteins play a critical role in γ-carboxylation, a posttranslational modification that is essential for the proper function of vitamin K-dependent proteins. Timely and accurate diagnosis is essential to differentiate VKCFD from other genetic and acquired disorders, and genetic testing is required to identify the specific variant.The primary treatment for VKCFD is the administration of vitamin K, with transfusions of fresh frozen plasma often required during surgery or in cases of severe bleeding. In certain situations, alternative therapies such as prothrombin complex concentrates (PCCs) or a combination of recombinant activated factor VII and vitamin K may be considered. With appropriate treatment, individuals with VKCFD generally have a good clinical outcome, and the condition has a limited impact on their quality of life. This article presents a comprehensive review of all 57 VKCFD cases documented in the literature, as well as 4 new, unpublished cases from France.
Keywords: VKCFD; GGCX; VKORC1; bleeding; vitamin K-dependent coagulation factors